(untitled) (The New Uzbekistan Journal of Medicine, 2025)
This article analyzes the morphological features of myocardial angiogenesis and mechanisms of its disruption in experimental diabetes. The studies analyzed data obtained on the basis of animal models induced by streptozotocin and alloxan, as well as genetic diabetes models. Histological, immunohistochemical, electron microscopic and molecular biological methods were used to assess myocardial angiogenesis. The results showed that a decrease in VEGF expression, a decrease in endothelial NO-synthase activity, a significant decrease in capillary density and suppression of the PI3K/Akt signaling pathways against the background of diabetes lead to insufficient development of angiogenesis. Also, endothelial dysfunction and increased fibrosis processes were noted. The results obtained serve as an important theoretical basis for a deeper understanding of the pathogenesis of diabetic cardiomyopathy and the development of new treatment approaches.